2015
DOI: 10.1111/bju.13206
|View full text |Cite
|
Sign up to set email alerts
|

Low testosterone level is an independent risk factor for high‐grade prostate cancer detection at biopsy

Abstract: ObjectiveTo investigate the relationship between low testosterone levels and prostate cancer detection risk in a biopsy population. Patients and MethodsIn all, 681 men who underwent initial 12-core transrectal prostate biopsy at our institution were included in this retrospective study. Patients were divided into groups with low (<300 ng/dL) and normal testosterone levels (≥300 ng/ dL). Clinical and pathological data were analysed. ResultsAmong 681 men, 86 men (12.6%) had low testosterone levels, 143 (32.7%) h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 37 publications
(53 reference statements)
0
26
0
3
Order By: Relevance
“…This is in consonance with previous investigations. 9 Furthermore, low TT predicted high-grade PCa independently of age at diagnosis, which also opposes this conjecture. Rather, we believe that, according to the Saturation Model, patients with hypogonadism do not reach levels of testosterone necessary for physiological proliferation of the epithelium, leading to a greater risk of abnormal proliferation and differentiation, resulting in greater risk for high-grade cancer.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…This is in consonance with previous investigations. 9 Furthermore, low TT predicted high-grade PCa independently of age at diagnosis, which also opposes this conjecture. Rather, we believe that, according to the Saturation Model, patients with hypogonadism do not reach levels of testosterone necessary for physiological proliferation of the epithelium, leading to a greater risk of abnormal proliferation and differentiation, resulting in greater risk for high-grade cancer.…”
Section: Discussionmentioning
confidence: 96%
“…19 Similarly, Pichon et al showed, among subjects undergoing RP for PCa, that lower testosterone levels were associated with higher-grade PCa and with increased risk of GS upgrading from prostate biopsy to specimens from surgery. 20 Park et al 9 demonstrated a correlation between hypogonadism and unfavorable outcomes in prostatic biopsies, such as increased incidence of GS ≥ 8. Several studies, despite adopting different thresholds for the definition of hypogonadism, have confirmed an association between low testosterone levels and adverse characteristics and outcomes for PCa, including higher Gleason score, 21,22 higher pathological stage 10,22 and increased risk for disease progression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…24 We also examined mental health conditions that have been linked with low testosterone levels, including depression, 25 dementia, 26 schizophrenia, 27 and alcohol abuse. 28 We assessed obesity as a predictor, stratifying patients by body mass index (BMI).…”
Section: Independent Variables: Comorbid Conditions and Medicationsmentioning
confidence: 99%
“…In a recent study of 681 men undergoing a 12-core prostate biopsy, low testosterone level was found to be an independent risk factor for high-grade prostate cancer. 7 Similarly, Garcia-Cruz et al found that low pretreatment testosterone levels were significantly related to poor prognostic factors. 8 While the aetiology of low testosterone in high-grade prostate cancer patients remains uncertain, the body of evidence for this relationship continues to grow, leading some to suggest that monitoring testosterone levels prior to biopsy may provide prognostic information.…”
Section: Wisdom Challengedmentioning
confidence: 95%